Can the accepting foreign clinical data policy improve innovation investment of pharmaceutical firms? Empirical evidence from China - Jiang, Mengjuan; Huang, Jingjing; Wang, Su; Fan, Yulu; Chen, Yuwen (Frontiers in Public Health, 2025)
IntroductionIn October 2017, China initiated adjustments to the registration procedures for imported drugs to promote accessibility to overseas drugs. In support of this decision, the National Medical Products Administration (NMPA) issued a technical guideline regarding accepting foreign clinical trial data in July 2018. Collectively referred to as the accepting foreign clinical data policy, these measures have accelerated the influx of overseas drugs into China.MethodsUsing the panel data from 104 A-share pharmaceutical listed firms between 2013 and 2024, this study conducted a difference-in-differences model to explore the impact of this policy on the innovation investment of Chinese pharmaceutical firms and further analyzed the underlying moderating effect.ResultsThe results demonstrate a significantly positive effect of this accepting foreign clinical data policy on pharmaceutical firms’ innovation investment, which is verified with the parallel trend and robustness tests. Further analysis indicates that corporate absorptive capacity positively moderates the relationship between the policy implementation and innovation investment. In addition, the heterogeneity analysis suggests that this policy has a more significant effect on firms that are non-state-owned, engage in new drug research and have strong market power.DiscussionThis study serves as a significant supplement to the current literature regarding the accepting foreign clinical data policy and innovation investment, providing valuable insights for policymakers and R&D decision-makers in the pharmaceutical sector.